A human rights analysis of clustered regularly interspaced short palindromic repeats germline-editing for disease prevention - Lance Garrett Shaver; Amit Sundly; Abdullah Omar Saif (Wolters Kluwer Medknow Publications, 2020)
Our purpose is to discuss ethical concerns with disease prevention applications of CRISPR germline editing using a human rights approach. If applied towards furthering health, these tools may aid to prevent diseases, thereby improving health and reduce suffering. On the other hand, commercialization of this technology, such that it becomes accessible only to the wealthy few, may have the opposite effect. We argue that caution needs to be taken against the use of germline-editing technology for disease prevention, as unequal access to the technology might negatively impact the health of the population by perpetuating socioeconomic inequality. What were once diseases and immunities of chance could soon become diseases of the poor and immunities of wealth. Hence, if germline editing is to be used for disease prevention, commercialization must be resisted, and efforts must be made to make it available and accessible within the human rights framework.